Conservation of endangered and rare plants requires strategies additional to deer‐proof fencing for conservation of sub‐alpine plant diversity. Issue 1 (25th December 2020) - Koyama, Asuka; Uchida, Kei; Ozeki, Masaaki; Iwasaki, Takaya; Nakahama, Naoyuki; Suka, Takeshi
Abstract: Questions: Deer‐proof fencing is an essential conservation tool to protect and recover plant species diversity in deer‐overbrowsed ecosystems, including species‐rich sub‐alpine grasslands. However, community‐level conservation tools (such as fencing) may be insufficient for single‐species conservation, particularly for non‐target endangered or rare species that are sparsely distributed. We examined whether fencing that can protect and recover total plant species richness also benefits non‐target endangered or rare species. Location: A sub‐alpine semi‐natural Kirigamine grassland in Nagano Prefecture, Japan. Methods: We conducted two complementary plant surveys (typical vegetation survey using 1‐m 2 sampling units and flowering survey using 150‐m 2 sampling units) to account for scarce species. We examined the community‐level responses (species richness, flowering species richness, and flowering abundance) of all species and endangered or rare species and the species‐level responses (occurrence and flowering abundance) of each species to deer fences. Results: Fencing benefited not only the community‐level response of all species, but also that of endangered or rare species. As species‐level responses, about half of 43 endangered or rare species had greater flowering abundance inside the fences than outside, but only three of them showed a positive effect on their occurrence. These results suggest that once an endangered or rare species has disappeared, it may be difficult to recover. Conclusions: Continued placement of deer fences is necessary to protect community‐level plant species richness of sub‐alpine endangered and rare species in deer‐overbrowsed ecosystems. We also highlight the necessity of additional strategies focusing on non‐target individual species across broad areas outside fences. Abstract : Deer‐proof fencing may be insufficient for conservation of endangered or rare species that are sparsely distributed across a landscape. In a sub‐alpine semi‐natural grassland, deer fencing, which benefited total plant species richness, had no positive effect on the occurrence of most endangered and rare species. We highlight the necessity of additional conservation strategies focusing on non‐target individual species especially outside the fences.